A PC-based shutter glasses controller for visual stimulation using multithreading in LabWindows/CVI. (May 2017) - Gramatikov, Ivan; Simons, Kurt; Guyton, David; Gramatikov, Boris
Highlights: Newer methods for treating amblyopia use shutter glasses to occlude the strong eye. Needed is a computer-based system to perform liquid crystal shuttering in laboratory and clinical settings, possibly also for home use. In order to achieve good timing performance in a bidirectional system under Windows, a multithreading programming technique with data protection is needed. We developed software based on multithreading under LabWindows/CVI (National Instruments) that allowed efficient real-time performance with inexpensive hardware. Abstract: Background and objectives : Amblyopia, commonly known as "lazy eye, " is poor vision in an eye from prolonged neurologic suppression. It is a major public health problem, afflicting up to 3.6% of children, and will lead to lifelong visual impairment if not identified and treated in early childhood. Traditional treatment methods, such as occluding or penalizing the good eye with eye patches or blurring eye drops, do not always yield satisfactory results. Newer methods have emerged, based on liquid crystal shutter glasses that intermittently occlude the better eye, or alternately occlude the two eyes, thus stimulating vision in the "lazy" eye. As yet there is no technology that allows easy and efficient optimization of the shuttering characteristics for a given individual. The purpose of this study was to develop an inexpensive, computer-based system to perform liquid crystal shuttering in laboratory and clinical settings to help "wake up" the suppressed eye in amblyopic patients, and to help optimize the individual shuttering parameters such as wave shape, level of transparency/opacity, frequency, and duty cycle of the shuttering. Methods : We developed a liquid crystal glasses controller connected by USB cable to a PC computer. It generates the voltage waveforms going to the glasses, and has potentiometer knobs for interactive adjustments by the patient. In order to achieve good timing performance in this bidirectional system, we used multithreading programming techniques with data protection, implemented in LabWindows/CVI. Results : The hardware and software developed were assessed experimentally. We achieved an accuracy of ±1 Hz for the frequency, and ± 2% for the duty cycle of the occlusion pulses. We consider these values to be satisfactory for the purpose of optimizing the visual stimulation by means of shutter glasses. The system can be used for individual optimization of shuttering attributes by clinicians, for training sessions in clinical settings, or even at home, aimed at stimulating vision in the "lazy" eye. Conclusions : Multithreading offers significant benefits for data acquisition and instrument control, making it possible to implement time-efficient algorithms in inexpensive yet versatile medical instrumentation with only minimum requirements on the hardware.